Revalorization, characterization and application of tofu industry by-product ‘okara’ as a food ingredient : a thesis presented in partial fulfilment of the requirements for the degree of Master of Food Technology, Massey University, New Zealand - Limonchi Pina, Mariana (Massey University, 2025)
The potential of revalorising okara into a powder for use in various food products has been researched in the literature, but no universal consensus has been achieved. Some studies have focused on drying small quantities of okara under different conditions, while others have attempted to substitute wheat flour with okara powder, often with limited success or by combining it with other grains to form composite flours. This project aimed to characterize powders obtained under varying drying conditions to identify the optimal method in terms of nutritional value, functionality and efficiency. Okara powder was then used in bread, cookies and as bread crumbs to maximize the substitution of wheat flour. Two drying methods were tested: freeze-drying and convection oven drying. For convection oven drying, six different temperatures (50, 60, 70, 80, 90 and 100°C) were evaluated to determine their effects on the physicochemical characteristics of okara powder. A total of 580 g of fresh okara was dried per trial to simulate industrial conditions where much larger quantities are processed. Proximate analysis was conducted for each drying treatment. The results showed no significant differences in ash, protein, or fat content across drying conditions. The physical properties of the powders, such as colour, particle size distribution as a powder and as suspension, water activity, water-holding capacity, solubility, bulk density, tapped density, Carr Index and flowability, were also assessed, as these influence food formulation and development. The best drying conditions were determined based on drying time, water activity, water-holding capacity, particle size, and flowability. Convection oven drying at 90 °C and 70 °C was identified as optimal due to the quick drying time, and low water activity (e.g. improved stability against microbial growth and lipid oxidation). Although freeze-drying provided superior water-holding capacity, it required significantly more time and resulted in less stable powders in terms of moisture and water activity. Okara powder was then incorporated into its use in bread and cookies at varying concentrations. Okara powder and okara bread crumb were also tested as a coating agent for frying vegetables. For bread, preliminary trials with okara substitution levels (10, 25 and 50 %) of wheat flour showed that a maximum substitution level of 20% (okara-to wheat flour ratio of 20:80) was feasible. Hydration levels of 80%, 90% and 100% were tested, with 100% hydration yielding the best results in terms of height, colour, and textural properties due to complete protein hydration and minimal interference from fibre. For cookies, okara powder was used as the sole flour. The formulation of cookies avoided allergens apart from soy by excluding eggs and dairy, substituting with chia seed gel and coconut shortening. Three formulations were compared (V1, V2, V3) were developed, varying corn flour and fat content to address surface cracks caused by poor binding. The best formulation, V2, contained higher fat and less okara powder., resulting in improved binding and lower hardness, a desirable trait for biscuits. Although informal testing was conducted, formal sensory evaluation was not performed, which would have provided valuable insights into flavour, texture and overall acceptability. Future studies should include sensory evaluations to assess flavour, odour, soybean aftertaste, texture, and consumer acceptance. Additionally, determining the nutritional composition of the okara-containing bread and cookies compared to wheat flour-based products would provide further justification for okara revalorization. This project highlights the impact of drying treatments on okara powder functionality, new application levels in breads and cookies, and the critical role of water and fat in formulations using okara.
Keywords: 300607 Food technology